2018
DOI: 10.1097/scs.0000000000004078
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Migraine Headache

Abstract: Migraine surgery has been recently reported as an alternative to medical management to provide long-term relief in migraine sufferers. A prospective study was designed wherein patients diagnosed with migraine were screened for surgery by injecting botulinum toxin type A at the primary trigger site. Surgery consisted of corrugator supercilii muscle resection to decompress supra-trochlear and supra-orbital nerves with avulsion of zygomaticotemporal branch of trigeminal nerve. Using pre and postsurgery questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…The non-response of all patients to commonly used medical treatments ( 3 ), patient-reported relief of migraine symptoms with medical cannabis use, and biological plausibility for how MC may work to treat migraines have contributed to the increased interest. It is also difficult to predict which patients will benefit from surgical procedures for chronic migraine, with some patients showing no improvement post-operation ( 6 , 7 ). As the number of states in the United States approving marijuana for medical use continues to increase, likely, migraine sufferers may choose cannabis to relieve their pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The non-response of all patients to commonly used medical treatments ( 3 ), patient-reported relief of migraine symptoms with medical cannabis use, and biological plausibility for how MC may work to treat migraines have contributed to the increased interest. It is also difficult to predict which patients will benefit from surgical procedures for chronic migraine, with some patients showing no improvement post-operation ( 6 , 7 ). As the number of states in the United States approving marijuana for medical use continues to increase, likely, migraine sufferers may choose cannabis to relieve their pain.…”
Section: Discussionmentioning
confidence: 99%
“…To provide relief for patients with chronic migraine, surgical management in the form of peripheral nerve decompression has been reported with some success. Although 47% of patients who had surgery reported complete elimination of migraine, some people with chronic migraine did not have any benefits, despite the risks of surgical exposure ( 6 , 7 ). This has led both physicians and patients to try dietary and herbal remedies, including the use of medical cannabis (MC) for migraine treatment ( 4 , 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A new hypothesis showed that zygoma-correlated PTH might be associated with auriculotemporal nerve (ATN) and zygomaticotemporal nerve (ZTN) injury [17,18]. Anatomically, both nerve pathways are extremely close to the zygomatic arch.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity in data and outcome reporting was high between studies. With the exception of Janis et al (39), Raposio et al (12), Guyuron et al (40), and Jose et al (41), studies did not report in detail whether unilateral or bilateral procedures were performed, therefore no further analysis based on laterality of the procedure was made. Six out of 14 studies report performing surgery on three or more surgical sites, among which are the three RCTs.…”
Section: Methodsmentioning
confidence: 99%